Evaluation of the program HEALTHY TEETH after Four Years of Implementation at the Primary Schools in the Czech Republic - I. Lekešová; L. Mrklas (Czech Dental Chamber, 2005)
The aim of the educational program HEALTHY TEETH is to improve the oral health of the children and youth and consequently to create the preconditions for improvement of the oral health of the adults in the coming years. The program consists of the Manual for Teachers, where vocational texts concerning oral health are publishing and the Work Sheets for Pupils, that interactively explain to children the dental care for deciduous and permanent teeth. The program was distributed to all primary schools in the Czech Republic and covers 605 007 children.The introduced intervention program can be evaluated only after certain period of time, these have been in practice. The first indications of the intervention program HEALTHY TEETH in the knowledge and attitudes of school children and their teachers to oral health have been evaluated after the period of four years, when the program at primary school was implemented. The epidemiological survey of children of fifth classes in the year 2004 pointed out the trend of decreasing of dental caries experience in the Prague children by 31 %. While we recorded decline of dental caries experience, dental status especially of children in Prague has been alarming. Of the total number of examined children in Prague only 9% were fully treated, and almost two thirds of them needed dental care. The authors are of the opinion that only way to solve this situation is to educate, inform and motivate both, the children and their parents to change their attitudes to oral health.